The Temporal Instability of Resting State Network Connectivity in Intractable Epilepsy. Issue 1 (15th September 2016) - Robinson, Lucy F.; He, Xiaosong; Barnett, Paul; Doucet, Gaёlle E.; Sperling, Michael R.; Sharan, Ashwini; Tracy, Joseph I.
Abstract: Objective: Focal epilepsies, such as temporal lobe epilepsy (TLE), are known to disrupt network activity in areas outside the epileptogenic zone [Tracy et al., 2015]. We devised a measure of temporal instability of resting state functional connectivity (FC), capturing temporal variations of BOLD correlations between brain regions that is less confounded than the "sliding window" approach common in the literature. Methods: We investigated healthy controls and unilateral TLE patients (right and left seizure focus groups), utilizing group ICA to identify the default mode network (DMN), a network associated with episodic memory, a key cognitive deficit in TLE. Our instability analyses focused on: (1) connectivity between DMN region pairs, both within and between TLE patients and matched controls, (2) whole brain group differences between region pairs ipsilateral or contralateral to the epileptogenic temporal lobe. Results: For both the whole brain and a more focused analysis of DMN region pairs, temporal stability appears to characterize the healthy brain. The TLE patients displayed more FC instability compared to controls, with this instability more pronounced for the right TLE patients. Significance: Our findings challenge the view that the resting state signal is stable over time, providing a measure of signal coherence change that may generate insights into the temporal components of network organization. The precuneus was the region within the DMN consistently expressing this instability, suggesting this region plays a key role in large scale temporal dynamics of the DMN, with such dynamics disrupted in TLE, putting key cognitive functions at risk. Hum Brain Mapp 38:528–540, 2017 . © 2016 Wiley Periodicals, Inc.